Working Paper 5: Poverty and corruption: About poorer and richer ways of life (Basel Institute on Governance Working Papers, 2008)
The Millennium Development Goals were adopted by the global community under the aegis of the UN in 2000. The first of these goals aims at halving absolute poverty of the about 1.1 billion people who live on less than 1 US dollar a day.Although poverty reduction has always been an important concern of development policy, the Millennium Development Goals have brought it back onto centre stage with renewed vigour, in that joint efforts to reduce poverty worldwide has become a moral as well as financial obligation of the global community. Just a glance at the global development indicators reveals how urgent the renewed efforts to fight extreme poverty, especially – and not surprisingly – in least developed countries.According to the UN statistics the number of persons living in extreme poverty has decreased slightly between 1990 and 2001; but it is still estimated that worldwide still approximately one billion people live on less than 1 US dollar a day.